Calc–silicate xenolith – magma interactions in the Rustenburg Layered Suite, Bushveld Complex - Koovarjee, Bavisha (My University, 2022)
The mafic-ultramafic Rustenburg Layered Suite (RLS) of the 2.05 Ga Bushveld Complex hosts xenoliths ranging in size from a few centimetres to tens of kilometres and comprising a variety of rock types derived principally from the chemical and clastic sedimentary rocks of the Transvaal Supergroup. This study investigates a rare case of a calc-silicate xenolith from an underground exposure at Rowland Shaft, Lonmin Platinum, near Marikana in the Western Limb, and drillcores through xenoliths in the Platreef in the Northern Limb on Zwartfontein Farm with the specific aim of investigating interactions between the xenoliths and RLS magma. In the Marikana xenolith, Perple_X modelling of the peak assemblage of monticellite + forsterite + spinel indicates Tmax conditions between 975 and 1125 °C at P between 0.6–1.6 kbar and XCO2 ~1. Centimetre-thick forsterite- and spinel-rich layers on the western edge of the xenolith are interpreted primarily as relict sedimentary layering; however, a vesuvianite-rich rim is interpreted as the product of hydrous retrograde fluid infiltration (XCO2 < 0.1) at T ~400–700 °C. The xenolith is hosted in mottled anorthosite of the Upper Critical Zone but is flanked by an ~25 cm wide contact zone that contains several small (<10 cm) calc-silicate fragments displaying the same peak assemblage as the main xenolith. These fragments are also surrounded by vesuvianite and/or vesuvianite + grossular symplectites. The matrix of the contact zone comprises almost pure anorthite plagioclase (An99) and Ca-Tschermak clinopyroxene with wollastonite exsolution lamellae. The plagioclase and pyroxene display a pseudo-ophitic texture, which is partially replaced by thin grossular coronas. Also present in the matrix are discrete grains of poikilitic uvarovitic garnet cored by chromite grains. In addition to the calcsilicate fragments, the contact zone contains several irregular-elongate garnet masses and a clast comprising 3 disrupted cm-scale chromitite stringers. EPM and LA-ICP-MS analysis of the “chromite” grains shows zoning from Cr-rich cores to rims characterised by Al and Fe3+ that resemble the spinels within the calc-silicate xenolith, suggesting increased hybridisation of the magmatic system during their growth. Cr-rich garnet similarly shows core to rim zonation from uvarovitic and grossularitic compositions. When combined with the unusually calcic plagioclase and the Ca-Al-Fe3+ clinopyroxene, these features are consistent with crystallisation of a hybrid magma that became increasingly contaminated by a xenolith component, with concomitant increase in oxygen fugacity. Bulk-rock XRF, micro-XRF and stable isotope data confirm that length-scales of chemical interaction ranged from cm to dm scale and may have varied, depending on specific elements. Overall, however, decarbonation of the xenolith resulted in a Mg-silicate-rich restite and produced the unusual calcic mineral compositions in the contact zone. The δ18O values of 7.62‰–12.67‰ and 8.63‰–9.8‰ for the plagioclase and pyroxene, respectively, in the contact zone contrast with those in the mottled anorthosite (6.42–6.62‰ and 5.81‰). The unusual location of the 7 cm thick chromitite stringer in the contact zone is interpreted as disruption and entrainment of a portion of the UG1 chromitite layer, which lies 20 m stratigraphically above the xenolith, as the xenolith sank through the partially crystalline magma as a result of decarbonation-driven density increase. Migration/displacement of the xenolith is supported by the steep dip and near-orthogonal strike of bedding in the xenolith relative to the RLS layering. Although peak monticellite + forsterite + diopside + spinel assemblages are preserved locally, calc-silicate xenoliths in the Platreef in the Northern Limb of the Bushveld Complex show strong retrograde re-equilibration, dominated by serpentine. While the intercalated Platreef is characterised by abundant parapyroxenite, which is interpreted as the product of crystallisation/metasomatism of hybrid magma and metasediment, the extreme calcic plagioclase and clinopyroxene compositions seen at Marikana are absent. However, stable isotopes show elevated δ18O values that agree with previous studies from the Northern Limb. Unlike at Marikana, the close proximity of the footwall sediments of the Transvaal Supergroup to the xenoliths suggests that discrete xenolith-magma interactions were overwhelmed by carbonates that have been completely digested by magma and voluminous fluids derived from prograde metamorphism of the Transvaal Supergroup footwall in the vicinity of the Zwartfontein cores.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2022